К изучению орибатид (Acariformes, Oribatei) прибрежной зоны Каневского водохранилища - Сергиенко, Г.Д. (Вестник зоологии, 1981)
62 species from the Oribatidae family are registered in different habitats of the Kanev reservoir littoral zone around the colony of Riparia riparia (L.). The most mass and distributed species are mentioned. Comparison of the Oribatidae fauna from the R. riparia nests with the Oribatidae fauna in the territory adjacent to the nest colony revealed 33 common species. The coefficient of community (Jaccard, 1902) was 0.35.